2022
DOI: 10.3171/2021.11.jns211851
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the residency application process: insights from neurological surgery during the pandemic virtual application cycle

Abstract: OBJECTIVE In this article, the authors describe the impact of the COVID-19 virtual match cycle and discuss approaches to optimize future cycles through applicant and neurosurgical education leadership insights. METHODS Anonymous surveys of neurosurgery program leaders (program directors and program chairs), program administrators (PAs), and 2020–2021 neurosurgery residency match applicants were distributed by the SNS, in conjunction with the Association of Resident Administrators in Neurological Surgery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…While prior authors 18,22,30 have shown survey data or provided recommendations that support or oppose socalled hybrid interviews, most of our respondents opposed this option. Our study's participants worried that hybrid interviews would promote inequities in applicant evaluation without significant benefits.…”
Section: Discussionmentioning
confidence: 86%
“…While prior authors 18,22,30 have shown survey data or provided recommendations that support or oppose socalled hybrid interviews, most of our respondents opposed this option. Our study's participants worried that hybrid interviews would promote inequities in applicant evaluation without significant benefits.…”
Section: Discussionmentioning
confidence: 86%
“…Virtual interviews resulted in a higher rate of matching at a student’s home institution [ 16 , 17 ]. There is evidence that some program directors are concerned that applicants from less prestigious schools are at a disadvantage in the era of virtual interviews and limited away rotations [ 12 ]. Both issues may have a substantial negative influence on diversity, equity, and inclusion, and the critical blending of cultures, both nationally and globally, through the match.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,22,30,31 Despite these reports, other studies demonstrated that implementation of virtual interviews effectively met overall program and applicant goals without significant differences in interview outcomes, including candidate and program assessment, ranking, and matching. 1,11,20,21,33,41,42 Despite their many limitations, these studies suggest that virtual interviews were generally wellreceived, and both programs and applicants appear to favor a hybrid interview model for the future. 1,9,16,21,22 However, no studies have yet compared hybrid models to in-person-only or virtualonly models.…”
Section: Challenges and Mitigation Strategiesmentioning
confidence: 91%
“…1,11,20,21,33,41,42 Despite their many limitations, these studies suggest that virtual interviews were generally wellreceived, and both programs and applicants appear to favor a hybrid interview model for the future. 1,9,16,21,22 However, no studies have yet compared hybrid models to in-person-only or virtualonly models. This could be one area for future exploration.…”
Section: Challenges and Mitigation Strategiesmentioning
confidence: 91%
See 1 more Smart Citation